Identification of bioactive ingredients from Cleome gynandra and the physicochemical study of their microencapsulation in beta-cyclodextrin - Maharaj, Vinesh J. (University of Pretoria, 2022)
Thesis (PhD (Chemistry))--University of Pretoria, 2022.